CONFRONTING CHALLENGES IN IMPLEMENTING E-PORTFOLIO VIA FACEBOOK IN A PHILIPPINE UNIVERSITY - Sipacio, Philippe (Universitas Pendidikan Indonesia, 2015)
Abstract: As an alternative assessment, e-Portfolio via Facebook (evFb) has been introduced at De La Salle University (DLSU) specifically at Department of English and Applied Linguistics (DEAL) primarily to respond to the demands of 21st century literacy. However, it was observed that despite the positive impact of evFb on students based on pilot-testing and related studies, there were still innumerable challenges that hindered its implementation. In this paper, these problems were identified, and were addressed using the lens of participatory development framework. Data were taken from interview and feedback forms of participants namely institution (represented by the department chair and project/program committee), implementers/teachers, and students, and were subjected to content analysis.Â The results showed three major issues classified as: (1) strong apprehension of students to publish their writing outputs on-line; (2) resistance of teachers towards FB as an educational tool; and, (3) concerns of institution as regards academic honesty and identity theft on-line. To confront these challenges and ensure effective implementation and sustainability of evFb at DEAL, improving participatory mechanisms was suggested and discussed. Finally, some opportunities and implications for policy relevant to evFb were also presented.